OPTIMALISASI WAKTU KERJA DAN JARINGAN PENDISTRIBUSIAN MAKANAN RINGAN MENGGUNAKAN MODEL ASSIGNMENT DAN HUNGARIAN - Sari, Gina Aulia; Herwanto, Dene; Nugraha, Billy (Inaque : Journal of Industrial and Quality Engineering, 2021)
The problems that occur in the home food industry is competition and raw material prices are not stable. The purpose of this study is to determine the assignment of the employee with his job and distribution to any point of destination by the shortest distance. The research Model used is the assignment, networking and using the help of software programs operations management – quantitative methods (POM-QM) for windows. In addition, the data collection technique done in several ways, namely interview, observation and recording schedule. The results of this research to obtain optimal results for the five employees based on a suitable job. Each employee are employee 1 with the type of occupation fry and takes 400 minutes. Employee 2 with the type of work to mix the marinade and takes 15 minutes. Employee 3 with this type of work gives the herbs and takes 30 minutes. Employee 4 with the type of work wrap up and takes 400 minutes. While the employee 5 with the type of work pack and takes 300 minutes. In addition the distribution to the point of destination with the shortest path produces the distance 148,9 km.